AN INTELLIGENT DECISION SUPPORT SYSTEM BASED ON IMAGE PROCESSING FOR EVALUATING OF THE ENDOSCOPIC IMAGES - Sengur, Abdulkadir; Turkoglu, Ibrahim; Ince, M. Cevdet (Pamukkale Univ, 2009)
In this study, a decision support system which helps the physician to determine the location of a polyp on the colonoscopic video images is presented. The system is composed of neural network classifier and features extracted from wavelet transform co-occurrence matrices. The proposed methodology is applied to a sequence of colonoscopic video frames which have normal and abnormal formations. The application results are evaluated with respect to the sensitivity and specificity analysis. As a result of the evaluation criterion, 90.2 % sensitivity and 88.7 % specificity values are obtained by using statistical features of the wavelet transform co-occurrence matrices and neural networks.
Keywords: Colonoscopic images; Polyp; Wavelet transform; Co-occurrence matrix; Artificial neural networks